2019
DOI: 10.31447/as000032573.2019233.07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and fostering transparency in local administrations

Abstract: Evaluating and fostering transparency in local administrations. The methods used to evaluate the transparency of local administrations present notable differences that are influenced by national legislation and administrative characteristics. Consequently, it is difficult to formulate a valid international procedure to obtain a global picture. We have conducted a comparative analysis of the procedure developed by Transparency and Integrity in Portugal with that designed by the Laboratory of Journalism and Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This method was adapted to apply it also to the cases of Ecuador [29] and Colombia [30]. This involved studying the legislation regarding the organization of public administrations, transparency and the right of access to information in those countries, evaluating the transparency and quality of the information published on their websites and carrying out a comparative analysis with other evaluation procedures of active transparency in local administrations of other countries based on diverse disciplinary approaches [31], using both published studies [32] and the sites where national and international organizations present their results and methods.…”
Section: Objectives and Methodsmentioning
confidence: 99%
“…This method was adapted to apply it also to the cases of Ecuador [29] and Colombia [30]. This involved studying the legislation regarding the organization of public administrations, transparency and the right of access to information in those countries, evaluating the transparency and quality of the information published on their websites and carrying out a comparative analysis with other evaluation procedures of active transparency in local administrations of other countries based on diverse disciplinary approaches [31], using both published studies [32] and the sites where national and international organizations present their results and methods.…”
Section: Objectives and Methodsmentioning
confidence: 99%
“…As far as transparency is concerned, our research has revealed that only 55.2% of municipal websites display their mayors' biographies and 96% publish council meetings official records. There is still some work to be done regarding councillors' income declarations (only 8.4% display them) and financial transparency (for more statistics see Tavares and Sousa, 2018;Rodríguez-Navas and Breijo, 2019). Definitely a high percentage of municipal representatives don't believe in the concept of open data.…”
Section: Transparency and The Use Of Ictmentioning
confidence: 99%
“…These results indicate the importance of institutional and other economic factors that can hinder the implementation of digital strategies. In addition, in such national comparisons, the importance of analytical bias deriving from applying methodologies designed on the basis of the political sciences or from a communicative perspective has been observed [21].…”
Section: Introductionmentioning
confidence: 99%